A subunit of protein kinase a regulates growth and differentiation in the fungus mucor circinelloides - Ocampo, J. (2009)
The cyclic AMP (cAMP)-dependent protein kinase A (PKA) signaling pathway plays a role in regulating development, growth, and virulence in a number of fungi. To determine whether PKA plays a similar function in zygomycete fungi, a mutant of Mucor circinelloides was generated that lacks pkaR1, one of the regulatory subunits of PKA. The mutant showed a reduction in growth and alterations in germination rates, cell volume, germ tube length, and asexual sporulation. The lack of pkaR1 gene resulted in a highly decreased, but not null, cAMP binding activity and in a protein kinase activity that was still dependent on cAMP, although with a higher -/+ cAMP activity ratio, suggesting the existence of other cAMP binding activities. Consequently, three proteins analogous to pkaR1 were predicted from the recently sequenced genome of M. circinelloides and were named pkaR2, pkaR3, and pkaR4. Two of the proteins, pkaR2 and pkaR3, with cAMP binding activity were isolated from the wild-type strain and identified by mass spectrometry. The expression of all genes was detected at the mRNA level by semiquantitative reverse transcription-PCR, and they showed a differential expression at different developmental stages. This is the first time that a fungus is reported to have more than one gene encoding the regulatory subunit of PKA. © 2009, American Society for Microbiology.